TECHNIQUES IN APPLIED MICROBIOLOGY - Reda, Fifi M., contributor 636287; El-Mekkawy, Rasha M., contributor 636288; Hassan, Noha S., contributor 636289; Yatoo, Mohd. Iqbal, contributor 636290; Parray, Oveas Raffiq, contributor 636291; Bhat, Riyaz Ahmed, contributor 636292; Muheet, contributor 636293; Gopalakrishnan, Arumugam, contributor 636294; Saxena, Archana, contributor 636295; Chakraborty, Sandip, contributor 541190; Tiwari, Ruchi, contributor 636296; Khurana, Sandip Kumar, contributor 636297; et al. (United Kingdom : Auris Reference Limited, 2020)
Microorganisms exist from where we can imagine to places we least expect e.g. outer spaceandtheDeadSea. Much of the global atmospheric oxygen is as a result of microbial activity. They also maintain the gut health by regulating the microflora, stimulating the development of the immune system, production and enhancement of some important nutrients and there seem to be a natural interdependence of life on microorganisms.